A1 Implementation of Fathul Muin's Teaching Material Books to Improve Santri's Competence at Tanwirunnida' Mungkid Islamic Boarding School, Central Java - Billy Eka Wardana (MultiTech Publisher, 2023)
Fathul Muin, book of fiqh by Sheikh Zakariya al-Ansari al-Maliki. Fiqh teaching material (Fathul Muin) consists of seven volumes, which have several components, including: First: discussing issues of chastity, prayer, fasting, zakat, pilgrimage and its laws. Second: Discussing the subject matter of buying and selling transactions and the law. Third: Marriage and its laws, finally war and its laws. Types of R&D research and data collection techniques using observation, interviews, and documentation. The results of the research on educational material on the Book of Fathul Muin are very useful for students in understanding Ushul al-Fiqh and jurisprudence lessons, and the learning process becomes very interesting in addition to the fact that this educational material can be studied independently and equipped with communicative language. Sources of supporting educational materials. The inhibiting factor is the lack of support from the parents of the students in carrying out the learning process and the diverse abilities of the students. The competence of students is expected to be able to connect three aspects, namely cognitive aspects, psychomotor aspects, and emotional aspects. This book is often used as the main teaching material in the study of Maliki jurisprudence and as a reference in solving everyday problems of Islamic law. With easy-to-understand language and complete explanations, Fathul Muin has become an important reference in the study and understanding of Islamic law.